Pericardial Effusion due to Primary Malignant Pericardial Mesothelioma: A Common Finding but an Uncommon Cause - Valery Istomin; David S. Blondheim; Simcha R. Meisel; Aaron Frimerman; Moshe Lapidot; Ronit Rachmilevitch (Case Reports in Medicine)
This case report describes a 37-year-old female who was admitted to our Emergency Department because of shortness of breath. On physical examination, she had dyspnea and tachycardia and blood pressure was 80/50 mmHg with a pulsus paradoxus of 22 mmHg. Neck veins were distended, heart sounds were distant, and dullness was found on both lung bases. Her chest X-ray revealed bilateral pleural effusion and cardiomegaly. On both computed tomography and echocardiography the heart was of normal size and a large pericardial effusion was noted. The echocardiogram showed signs of impending tamponade, so the patient underwent an emergent pericardiocentesis. No infectious etiology was found and she was assumed to have viral pericarditis and was treated accordingly. However, when the pericardial effusion recurred and empirical therapy for tuberculosis failed, a pericardial window was performed. A typical staining pattern for mesothelioma was found on her pericardial biopsy specimen. Since no other mesodermal tissue was affected, a diagnosis of primary malignant pericardial mesothelioma was made. Chemotherapy was not effective and she passed away a year after the diagnosis was made. This case highlights the difficulties in diagnosing this uncommon disease in patients that present with the common finding of pericardial effusion.